2020
DOI: 10.3390/su12083499
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Advanced Manufacturing Technologies on Green Innovation

Abstract: The main aim of this paper is to evaluate if manufacturing firms can boost their performance through green innovations. The literature on this topic shows contradictory findings. We have concentrated on the effect of advanced manufacturing technologies (AMT) on green innovations. To the authors’ best knowledge, this research is the first to examine the impact of a firm’s own AMT on green innovation and the firm’s performance at the same time. Green innovation in our research relates to green product innovation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 55 publications
0
16
0
1
Order By: Relevance
“…Tang et al found that the construction of telecom infrastructure will improve the informatization level of enterprises, increase the progress space and propagation speed of green technology, and thus have an incentive effect on green technology innovation [20]. From the micro level, scholars mainly analyze and discuss from the internal characteristics of enterprises, Palčič and Prester argue that advanced manufacturing technology contributes to both company performance and green innovation [21]. Ma et al found that executive characteristics have a positive impact on green technology innovation from the perspective of corporate governance, and when the whole team maintains a moderate fault line strength, it will lead to endogenous innovation dynamics from the top down [22].…”
Section: Research On Corporate Green Technology Innovationmentioning
confidence: 99%
“…Tang et al found that the construction of telecom infrastructure will improve the informatization level of enterprises, increase the progress space and propagation speed of green technology, and thus have an incentive effect on green technology innovation [20]. From the micro level, scholars mainly analyze and discuss from the internal characteristics of enterprises, Palčič and Prester argue that advanced manufacturing technology contributes to both company performance and green innovation [21]. Ma et al found that executive characteristics have a positive impact on green technology innovation from the perspective of corporate governance, and when the whole team maintains a moderate fault line strength, it will lead to endogenous innovation dynamics from the top down [22].…”
Section: Research On Corporate Green Technology Innovationmentioning
confidence: 99%
“…The manufacturing sector plays a dominant role worldwide in terms of social services and contribution to the development of regional, national, and global economy. In addition, it faces several megatrends and must therefore continuously innovate in order to improve the quality and sustainability of production [55]. Besides, many companies in this sector would not be able to operate without access to natural and environmental resources, which are crucial components of the majority of their production processes.…”
Section: Methodsmentioning
confidence: 99%
“…They adopted a three-step Ordinary Least Square for regression analysis. They proved that advanced manufacturing enterprises had contributed to corporate performance and green innovation [12]. Regarding the application of BPNN in prediction, Zhang (2019) introduced a production prediction model based on BPNN optimized by Particle Swarm Optimization (PSO) to cope with the shortcomings of predicting aquaculture production and export scale.…”
Section: Introductionmentioning
confidence: 99%